Do Winter Canola Hybrids and Open-Pollinated Varieties Respond Differently to Seeding Rate? - B. M. Showalter; K. Roozeboom; M. J. Stamm; G. Cramer (Kansas Agricultural Experiment Station Research Reports, 2017)
Several producers have turned to planting canola in 30-in. rows as a strategy to take advantage of residue management options (e.g. planter-mounted residue managers and strip tillage) to facilitate planting canola in high-residue cropping systems. Canola hybrids are gaining acres in the southern Great Plains and may require different management than the traditional open-pollinated cultivars. The objective of this study was to determine the effect of seeding rate on winter survival and yield of hybrid and open-pollinated winter canola cultivars in 30-in. and 9-in. rows. Experiments were conducted in 2013-2014, 2014-2015, and 2015-2016 at two K-State Research and Extension facilities. Treatments were four locally adapted cultivars (two hybrids and two open-pollinated cultivars) and three or five seeding rates for a total of twelve or twenty treatments in each experiment. Due to nearly complete winter stand loss of hybrids in the experiment planted in 2013, only open-pollinated cultivars were harvested. No experiments were harvested for yield in 2015 because of nearly complete stand loss in all treatments at all locations. In both row spacings, fall stands tended to increase with increasing seeding rates, and hybrids tended to establish more plants than open-pollinated cultivars. Differences in stands due to seeding rate were somewhat less evident in the spring, but stand differences due to cultivars were more evident. Winter survival tended to increase as the number of plants present in the fall decreased, whether that was due to seeding rate or other factors. Bloom occasionally was delayed, and harvested seed moisture tended to be greater when fewer plants were present in the spring, likely due to a greater percentage of buds forming on branches. Seeding rate had a minimal impact on yields in 30-in. rows, with hybrids and open-pollinated cultivars responding similarly in most cases. In 9-in. rows, seeding rate did not affect yields in 2014. In 2016, both hybrids and open-pollinated cultivars maximized yield at 300,000 seeds per acre in 9-in. rows, but hybrids maintained greater yields than open-pollinated cultivars at sub-optimal seeding rates.
Keywords: canola; seeding rates; row spacing; hybrids; open-pollinated